Software Infrastructures for smart spaces : bridging the gap between global computing and situated devices - José, Rui (2007)
In this position paper, we argue that a wide deployment of Pervasive Computing should combine two complimentary approaches. The first is to make extensive use of global services as a way to provide functionality to any place without having to create dedicated services. The second is to leverage situated displays as a general purpose gateway between those services and the physical environment.